The effect of poly(vinylidene fluoride) binder on the electrochemical performance of graphitic electrodes. (July 2021) - Rajeevan, Sreelakshmi; John, Sam; George, Soney C
Highlights: Highly efficient graphitic electrodes are designed and prepared via a simple solvent evaporation method. The PvG5 electrode showed highest specific capacitance of 16.2 /g at a scan rate of 10 mV/s and 13.11 F/g at a current of 0.00001 A. The specific surface area calculated from BET analysis for the PvG5 electrode is 640.2 m 2 /g which is 30-fold compared to pure graphite. Approximately 87% of capacitance retention was observed for PvG5 electrode after 1000 cycles. Abstract: The influence of poly(vinylidene fluoride) (PVDF) as a binder on enhancing the electrochemical performance of graphite (G) electrodes was studied. The structural analysis of prepared composite electrodes was studied using X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The electrochemical properties of the PVDF/Graphite composite electrodes were studied using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). The SEM images of graphitic electrodes proved the binding ability of PVDF. PVDF provide a compact arrangement to the graphitic electrodes. The electrochemical analysis showed that among graphitic electrodes, PVDF with 5 g graphite i.e., PvG5 electrode has an ideal capacitor behaviour with good cycling stability and low internal resistance. The highest specific capacitance of 16.2 F/g at a scan rate of 10 mV/s and 13.11 F/g at a current of 0.00001 A was obtained for the PvG5 electrode. Furthermore, approximately 87% of capacitance retention was observed for PvG5 electrode after 1000 cycles. The specific surface area calculated from BET analysis for the PvG5 electrode is 640.2 m 2 /g which is 30-fold compared to pure graphite. The PvG5 electrode possess good electrochemical properties compared to pristine graphite and it is a promising electrode of electrical double layer capacitor (EDLC). Graphical abstract: Image, graphical abstract